Design and implementation of nonlinear integral backstepping control strategy for single-phase grid-connected VSI - Moussa Reddak; Abdelouahed Mesbahi; Ayoub Nouaiti; Abdelmajid Berdai (Institute of Advanced Engineering and Science, 2019)
This paper presents the design and the implementation of a nonlinear integral backstepping control strategy for a single-phase grid-connected voltage source inverter (VSI). The proposed control strategy aims to resolve the problem of the sinusoidal reference current tracking, to have a rapid transient response needed to deal with the transient incident such as grid voltage drops and to generate into the grid a current with fewer harmonics. These properties are verified by seeking the direction, the amplitude and the transient response of the injected grid current. An experimental VSI prototype is used to validate the effectiveness of the proposed controller, basing on a digital signal processor DSP microcontroller. The achieved results show that the well- obtained properties satisfy the grid current injection conditions.